2021
DOI: 10.3390/biology10020085
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Pentose Phosphate Pathway Enzyme 6-Phosphogluconate Dehydrogenase Plays a Key Role in Breast Cancer Metabolism

Abstract: The pentose phosphate pathway (PPP) plays an essential role in the metabolism of breast cancer cells for the management of oxidative stress and the synthesis of nucleotides. 6-phosphogluconate dehydrogenase (6PGD) is one of the key enzymes of the oxidative branch of PPP and is involved in nucleotide biosynthesis and redox maintenance status. Here, we aimed to analyze the functional importance of 6PGD in a breast cancer cell model. Inhibition of 6PGD in MCF7 reduced cell proliferation and showed a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Associated with this, Jiang et al have demonstrated that the inhibition of both the oxidative phase of the PPP and IDH enhances ROS levels in lung cancer cells [64]. Similarly, we have previously reported an increased glutamine consumption in breast cancer cells with ablated 6-phosphogluconate dehydrogenase, the third enzyme of the oxidative PPP [9], and that glutamine deprivation enhances ME flux in breast cancer cells [65], indicating strong crosstalk between glutamine metabolism and ox-PPP. Thus, we hypothesized that there might be a relation between G6PD and glutamine-dependent reactions for NADPH production.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Associated with this, Jiang et al have demonstrated that the inhibition of both the oxidative phase of the PPP and IDH enhances ROS levels in lung cancer cells [64]. Similarly, we have previously reported an increased glutamine consumption in breast cancer cells with ablated 6-phosphogluconate dehydrogenase, the third enzyme of the oxidative PPP [9], and that glutamine deprivation enhances ME flux in breast cancer cells [65], indicating strong crosstalk between glutamine metabolism and ox-PPP. Thus, we hypothesized that there might be a relation between G6PD and glutamine-dependent reactions for NADPH production.…”
Section: Discussionsupporting
confidence: 72%
“…We found that in both HT29 and HCT116 cell lines, the siG6PD pool decreased G6PD enzyme activity by over 80%, and western blot analysis demonstrated a visible decrease in the protein levels of this enzyme (Figure 2B,C and Supplementary Figure S1B). Several studies have shown that PPP has an essential role in cell growth and proliferation [9,10,[33][34][35][36]. Considering this, we examined the role of the G6PD enzyme in the proliferation of colon cancer cell models.…”
Section: G6pd Inhibition Alters the Proliferation Of Ht29 And Hct116 Cellsmentioning
confidence: 99%
See 3 more Smart Citations